Penilaian Guru untuk Mata Pelajaran Bahasa Indonesia pada Masa Pandemi Covid-19 di SDN Jurumudi 02 Tangerang - Rizkiah Amaliah (Edukasi Tematik: Jurnal Pendidikan Sekolah Dasar, 2021)
This study aims to identify and describe aspects of assessment, assessment techniques, and types of assessment used by teachers at SDN Jurumudi 02 Tangerang during the COVID-19 pandemic. This research is a type of qualitative research. The method used is descriptive. The research subjects were third grade teachers, fifth grade teachers, school principals, and school operators. Data collection techniques used by researchers are interviews, observation, and documentation. The results showed that the aspects of the assessment carried out by the teachers at the school included cognitive, affective, and psychomotor aspects, although the cognitive aspects were more dominated. The assessment technique used is an oral, written, performance, product, and portfolio assessment technique. The type of assessment used is the type of formative and summative assessment because in accordance with the learning activities the teacher can determine the students' abilities from the time of the learning process to the final results of student learning.